A comparison of Dignity Therapy narratives among people with severe mental illness and people with cancer. Issue 4 (7th March 2022) - Grassi, Luigi; Nanni, Maria Giulia; Caruso, Rosangela; Ounalli, Heifa; Chochinov, Harvey M.; Biancosino, Bruno; Testoni, Ines; Murri, Martino Belvederi; Bertelli, Tatiana; Palagini, Laura; De Padova, Silvia; Tiberto, Elisa
Abstract: Objective: To examine Dignity Therapy (DT) narratives in patients with severe mental illness (SMI) and a control group of cancer patients. Methods: 12 patients with SMI (schizophrenia, bipolar disorders, sever personality disorders) and 12 patients with non‐advanced cancer individually participated to DT interviews. DT was tape‐recorded, transcribed verbatim and shaped into a narrative through a preliminary editing process. A session was dedicated to the final editing process along with the participant, with a final written legacy (generativity document) provided to the participant. Interpretative Phenomenological Analysis was used to qualitatively analyze the generativity documents. Results: Patients with SMI and patients with cancer presented similar main narrative categories relative to dignity, such as "Meaning making", "Resources", "Legacy", "Dignity"; in addition, inpatients with SMI "Stigma" and inpatients with cancer "Injustice" emerged as separate categories. Patients in both groups strongly appreciated DT as an opportunity to reflect on their life story and legacy. Conclusions: The study showed that DT is a valuable intervention for people with SMI, grounded in a practical, person‐centered approach. All patients found DT as an opportunity to describe their past and present, highlighting changes in the way they relate to themselves and others. These results can guide implementation of DT in mental health settings for people with SMI, as it is for people with cancer. Key points: This study analyzed the narratives in patients with severe mental illness (SMI) and a control group of cancer patients All patients completed Dignity Therapy (DT), including creating a generativity document Patients with SMI and patients with cancer presented similar main narrative categories relative to dignity, such as "Meaning making", "Resources", "Legacy", "Dignity"; in addition, patients with SMI included "Stigma" and patients with cancer "Injustice" Results can guide implementation of DT in mental health settings for people with SMI